(untitled) (Teología, 2015)
This collaboration corresponds to the presentation of the Brazilian theologian in the Centenary of the Faculty of Theology of the Catholic University of Argentina. In his contribution he affirms that the way of life a local Church may become a sign for the whole Christian community. In this sense, the universal magisterium of Pope Francis, matured in the theological context of Latin America, is a service to the whole Universal Church, which invites to a commitment with the poor and various existential peripheries.